Urban potentials, Goražde 2012 - Andreja Benko (AR: Arhitektura, Raziskave, 2012)
A workshop is a form of learning, but also a working method for intensive work and learning in a short time which architects also like to use in their work. The method of implementing a workshop depends on the group and the anticipated outcomes. Each has its own educational objectives and targets that in combination lead to a common goal for all - the successful completion of the workshop. For an urban-architectural workshop, it is extremely important to observe and experience a space along with the local population. The correct coordination of a workshop, as well as the participants in it, is of the utmost importance. The preparation and implementation of an architectural workshop is a comprehensive project comprising several interdependent tasks. Collaboration, professionalism, businesses and the participation of the public characterising the workshop in the town of Goražde proved crucial and were the thread running through the workshop. This workshop is thereby a role model of cooperation between theory and practice.